(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
Core values of a school are fundamental beliefs and guiding principles that shape a student’s behavior, attitudes, skills, and knowledge leading to holistic development. While the school is proactive in promoting these, the researchers observed that students commit behaviors that do not reflect the school’s core values. Thus, this study aims to determine the development of core values among the respondents, and the factors that contribute to its development. This quantitative descriptive-correlational study surveyed 138 Senior High School students chosen using simple random sampling. Weighted mean and standard deviation was employed to analyze the level of development of core values among the respondents, and the extent of contribution of class interaction, school co-curricular activities, and general campus setting to its development. Regression analysis was utilized to measure the effect of the factors to the development of core values. The findings reveal that students exhibit strong ethical behavior, empathy, accountability, and commitment to academic integrity, with a willingness to contribute positively to their school and broader community. However, there is a slight variation in scores, notably lower in indicators related to reporting academic dishonesty and competition for academic achievement. Regression analysis revealed that there is a strong positive impact of class interactions, participation in co-curricular and extra-curricular activities, school policies, and campus initiatives on the development of core values among students. The results imply that the development core values are a result of continuous school engagements the students are part of. The researchers recommend strengthening classroom interaction, co-curricular activities, and school environment suitable for honing the school core values to the students.